In vitro Evaluation of Magnification and LED Illumination for Detection of Occlusal Caries in Primary and Permanent Molars Using ICDAS Criteria - Timucin Ari; Sahza Hatibovic Kofman; Nilgun Ari (MDPI AG, 2013)
Background: Early detection of occlusal caries in children is challenging for the dentists, because of the morphology of pit and fissures. Aim: The aim of the present study was to investigate the use of low-powered magnification (×2.5) and its association with LED headlight illumination for occlusal caries detection in primary and permanent molars using International Caries Detection and Assessment System (ICDAS) criteria.Methods: The occlusal surfaces of 36 extracted teeth (n=18 primary molars, n=18 permanent molars) were examined using ICDAS criteria with unaided visual examination, low-powered magnification and low-powered magnification plus LED headlight illumination. Three examiners evaluated one occlusal site per tooth twice independently with one week interval, using all methods. The teeth (n = 36) were sectioned and examined under light microscopy using Downer's histological criteria as the gold standard. Results: The weighted kappa values for inter- and intraexaminer reproducibility for the ICDAS examinations were almost perfect (Kappa values 0.72-0.96) in all three examination methods. The correlation with histology and overall AUC performance (0.96-0.98) of low-powered magnification plus LED headlight illumination was statistically significant in permanent molars. In primary molars, both low-powered magnification (0.82-0.90) and low-powered magnification plus LED headlight illumination (0.87-0.93) showed statistically significant correlation with histology and good to excellent AUC performance than unaided examination. Conclusion: Visual aids have the potential to improve the performance of early caries detection and clinical diagnostics in children.